1977
DOI: 10.1007/bf00439110
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on the effect of repeated electroconvulsive shock on the behavioural resposes of rats produced by increases in the functional activity of brain 5-hydroxytryptamine and dopamine

Abstract: Abstract. Following repeated electroconvulsive shocks (ECS) (once daily for 10 days), rats display enhanced hyperactivity responses to tranylcypromine and Ltryptophan, a procedure which increases brain 5-hydroxytryptamine (5-HT) concentrations, or to the suggested 5-HT agonist quipazine. The enhanced responses last for about 6 days following the last shock. Repeated sub-convulsive shocks did not produce this behavioural enhancement.Administration of indomethacin (2 mg/kg) 25 rain before the ECS did not prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
2

Year Published

1978
1978
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(31 citation statements)
references
References 20 publications
3
26
0
2
Order By: Relevance
“…Due to the small amount of flurothyl available it was decided to try 7 daily treatments rather than 10 as in our previous studies (Evans et al, 1976;Green et al, 1977).…”
Section: Effect Of Repeatedflurothyl Convulsions On Tranylcypromineilmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the small amount of flurothyl available it was decided to try 7 daily treatments rather than 10 as in our previous studies (Evans et al, 1976;Green et al, 1977).…”
Section: Effect Of Repeatedflurothyl Convulsions On Tranylcypromineilmentioning
confidence: 99%
“…Recently it has been demonstrated that repeated, but not single, electroconvulsive shocks (ECS), once daily for 7 or more days results in rats displaying enhanced behavioural responses to various procedures thought to stimulate central 5-hydroxytryptaminergic, dopaminergic or noradrenergic systems (Modigh, 1975;Evans, Grahame-Smith, Green & Tordoff, 1976;Green, Heal & Grahame-Smith, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now convincing evidence that repeated administration of electroconvulsive shock (ECS) to rats enhances the response in several 5-hydroxytryptamine-(5-HT)-mediated behavioural models (see, for example, Evans, Grahame-Smith, Green & Tordoff, 1976;Green Heal & Grahame-Smith, 1977; Green, Costain & Deakin, 1980; Lebrecht & Nowak, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…droxytryptamine (5-HT) agonists whilst mice show an Mice and rats also show an enhanced locomotor increased head-twitch response (Evans et al, 1976; response to dopamine agonists (Modigh, 1975;Evans Green et al, 1977;Lebrecht & Nowak 1980;Green et et al, 1976;Deakin et al, 1981) although there does al., 1983b). not appear to be any change in dopamine receptor number or dopamine-sensitive adenylate cyclase activity (Green et al, 1977;Bergstrom & Kellar, 1979; 'Correspondence Deakin et al, 1981).…”
Section: Repeated Administration Of Electroconvulsive Shockmentioning
confidence: 97%